Re-Clothing the Emperor: the Dead and Aliveness of Practice-Based Research in Performance - Freeman, John (Drama Australia, 2011)
This article questions whether practice-based submissions for PhD are chiefly problematised by their own immediacy and that issues of dissemination are secondary to issues of time. In suggesting research is linked to the unruly rhythms of creative practice, the article picks its own route through embodiment, institutional acceptance, truth, lies and punctuation, theatre influence, and tensions between permanence and ephemerality.